Isolation, fractionation and evaluation of the antiplasmodial properties of Phyllanthus niruri resident in its chloroform fraction - Ifeoma, Obidike; Samuel, Okhale; Itohan, Aboh Mercy; Adeola, Salawu Oluwakanyinsola (Asian Pacific Journal of Tropical Medicine, 2013)
Objective: To investigate the antiplasmodial activity of Phyllanthus niruri (P. niruri) methanol extract (ME) and its fractions in mice. Methods: P. niruri methanol extract and its chloroform, ethanol and aqueous portions were tested against chloroquine-sensitive Plasmodium berghei berghei. in early, established mid repository models of infection using Knight and Peter's 4-day suppressive model, Ryley and Peters curative model and Peters prophylactic model respectively. Results: Chemosuppression of parasitaemia (37.65%-50.53 %) was elicited by 100-400 mg/kg (b.w.) of ME. At doses of 100 mg/kg b.w., the chloroform fraction (F1) significantly (P<0.01) suppressed parasitaemia by 85.29%, while ethanol and aqueous fractions (F2 and F3, respectively) elicited 67.06% and 51.18% chemosuppression. The most active fraction, F1 was selected for further antiplasmodial screening. In established infection, ME reduced parasitaemia (15.81%-62.96%) while F1 significantly (P<0.01) reduced parasitaemia (44.36%-90.48%), with effects comparable to that of chloroquine (96.48%). The prophylactic antiplasmodial activity of ME (92.50% suppression) was also significant (P<0.01) and was more effective than pyrimethamine (85.00%). Additionally, cell membrane integrity of non-parasitized erythrocytes incubated with 125-500 mg/mL F1 was maintained. Conclusions: These findings indicate the antiplasmodial efficacy of P. niruri methanol extract, and the localization of this effect in its chloroform fraction.
Keywords: malaria; Phyllanthus niruri; Plasmodium

Profiling of metabolic alterations in mice infected with malaria parasites via high-resolution metabolomics - Chhibber-Goel, Jyoti; Shukla, Anurag; Shanmugam, Dhanasekaran; Sharma, Amit (Molecular and Biochemical Parasitology, 2022)
Background: Malaria infection can result in distinct clinical outcomes from asymptomatic to severe. The association between patho-physiological changes and molecular changes in the host, and their correlation with severity of malaria progression is not fully understood. Methods: In this study, we addressed mass spectrometry-based temporal profiling of serum metabolite levels from mice infected with Plasmodium berhgei (strain ANKA). Results: We show global perturbations and identify changes in specific metabolites in correlation with disease progression. While metabolome-wide changes were apparent in late-stage malaria, a subset of metabolites exhibited highly correlated changes with disease progression. These metabolites changed early on following infection and either continued or maintained the change as mice developed severe disease. Some of these have the potential to be sentinel metabolites for severe malaria. Moreover, glycolytic metabolites, purine nucleotide precursors, tryptophan and its bioactive derivatives were many fold decreased in late-stage disease. Interestingly, uric acid, a metabolic waste reported to be elevated in severe human malaria, increased with disease progression, and subsequently appears to be detoxified into allantoin. This detoxification mechanism is absent in humans as they lack the enzyme uricase. Conclusions: We have identified candidate marker metabolites that may be of relevance in the context of human malaria.
Keywords: Host response; Infectious diseases; malaria; metabolite; Plasmodium